Indonesian EFL Students’ Perceptions of AI-Based Chatbots in English Language Learning at The Secondary School Level - Andreansyah, Mochamad Rizky; Nugroho, Him'mawan Adi (English Education Department, 2025)
The rapid advancement of technology has brought transformative changes to the field of education, including English language learning. This study investigates Indonesian EFL secondary school students’ perceptions of AI-based chatbots in English language learning, guided by the Technology Acceptance Model (TAM). Employing a quantitative survey design, data were collected from 142 senior high school students across East Java who had prior experience using AI-based chatbots such as ChatGPT, Gemini, and Perplexity. The analysis explored five dimensions of TAM: Perceived Usefulness, Perceived Ease of Use, Positive Attitudes, Negative Attitudes, and Behavioral Intention. The results indicated generally favorable perceptions, with students reporting high ease of use and a positive outlook on chatbot-assisted learning, especially for reading and writing. However, they expressed moderate concerns regarding ethical risks, such as academic dishonesty and the need for supervision. Gender analysis revealed that female students reported significantly higher negative attitudes, while no significant differences were found across grade levels. These findings affirm the relevance of TAM in understanding technology adoption in EFL contexts and highlight the need for pedagogical strategies and digital literacy to ensure the ethical and effective integration of AI-based chatbots into formal language learning environments.